A model of liver carcinogenesis originating from hepatic progenitor cells with accumulation of genetic alterations. Issue 5 (16th September 2013) - Kim, Soo Ki; Nasu, Akihiro; Komori, Junji; Shimizu, Takahiro; Matsumoto, Yuko; Minaki, Yasuko; Kohno, Kenji; Shimizu, Kazuharu; Uemoto, Shinji; Chiba, Tsutomu; Marusawa, Hiroyuki
Abstract : Activation‐induced cytidine deaminase (AID) contributes to inflammation‐associated carcinogenesis through its mutagenic activity. In our study, by taking advantage of the ability of AID to induce genetic aberrations, we investigated whether liver cancer originates from hepatic stem/progenitor cells that accumulate stepwise genetic alterations. For this purpose, hepatic progenitor cells enriched from the fetal liver of AID transgenic (Tg) mice were transplanted into recipient "toxin‐receptor mediated conditional cell knockout" (TRECK) mice, which have enhanced liver regeneration activity under the condition of diphtheria toxin treatment. Whole exome sequencing was used to determine the landscape of the accumulated genetic alterations in the transplanted progenitor cells during tumorigenesis. Liver tumors developed in 7 of 11 (63.6%) recipient TRECK mice receiving enriched hepatic progenitor cells from AID Tg mice, while no tumorigenesis was observed in TRECK mice receiving hepatic progenitor cells of wild‐type mice. Histologic examination revealed that the tumors showed characteristics of hepatocellular carcinoma and partial features of cholangiocarcinoma with expression of the AID transgene. Whole exome sequencing revealed that several dozen genes acquired single nucleotide variants in tumor tissues originating from the transplanted hepatic progenitor cells of AID Tg mice. Microarray analyses revealed that the majority of the mutations (>80%) were present in actively transcribed genes in the liver‐lineage cells. These findings provided the evidence suggesting that accumulation of genetic alterations in fetal hepatic progenitor cells progressed to liver cancers, and the selection of mutagenesis depends on active transcription in the liver‐lineage cells. Abstract : What's new? The accumulation of stepwise genetic aberrations is a defining feature of cancer. To better understand this process in liver cancer, the present study leveraged the mutagenic ability of activation‐induced cytidine deaminase (AID) by using fetal hepatic progenitor cells from AID transgenic mice. The progenitor cells were transplanted into "toxin‐receptor mediated conditional cell knockout" mice, where they accumulated genetic alterations sufficient to induce liver tumor formation, for both HCC and cholangiocarcinoma. The landscape of accumulated alterations was revealed by whole exome sequencing. The findings lend support to the idea that cancer arises from tissue stem/progenitor cells.